2021
DOI: 10.3389/fimmu.2021.748573
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKM2-Mediated Immunometabolic Reprogramming on Development of Cytokine Storm

Abstract: The cytokine storm is a marker of severity of various diseases and increased mortality. The altered metabolic profile and energy generation of immune cells affects their activation, exacerbating the cytokine storm. Currently, the emerging field of immunometabolism has highlighted the importance of specific metabolic pathways in immune regulation. The glycolytic enzyme pyruvate kinase M2 (PKM2) is a key regulator of immunometabolism and bridges metabolic and inflammatory dysfunction. This enzyme changes its con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 215 publications
0
26
1
Order By: Relevance
“…Aerobic glycolysis is a crucial metabolic event for M1 macrophages accompanied by increased lactate production. PKM2 is one of the rate-limiting enzymes in glycolysis, which can rapidly regulate its metabolic activity by changing its distribution in cytoplasm and nucleus ( Liu et al, 2021 ). Accordingly, PKM2 in the colonic lamina propria of colitis mice were reduced after treatment with Shikonin (12.5 and 25 mg/kg) compared with DSS group ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic glycolysis is a crucial metabolic event for M1 macrophages accompanied by increased lactate production. PKM2 is one of the rate-limiting enzymes in glycolysis, which can rapidly regulate its metabolic activity by changing its distribution in cytoplasm and nucleus ( Liu et al, 2021 ). Accordingly, PKM2 in the colonic lamina propria of colitis mice were reduced after treatment with Shikonin (12.5 and 25 mg/kg) compared with DSS group ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…PKM2 is a key metabolic enzyme, which dimer and tetramer, although composed of the same monomer, play distinctly different roles. PKM2 tetramers, expressed mainly in the cytoplasm of proliferating cells, has high pyruvate kinase activity ( Zhang et al, 2019 ; Liu et al, 2021 ). However, phosphorylation of PKM2 by tyrosine 105 residue (Tyr-105) inhibits the tetramer activity and stabilizes the dimer structure, resulting in translocation to nucleus, where the dimer works mainly as protein kinase to active HIF-1α and mediate aerobic glycolytic metabolic reprogramming in pro-inflammatory macrophages and cancer cells ( Hitosugi et al, 2009 ; Palsson-McDermott et al, 2015 ; Shirai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic reprogramming of macrophage results in a high dependence of cellular energy metabolism on glycolysis to meet the high demands of macrophages to fight infection in an inflammatory environment. DC activation is often accompanied by upregulation of glucose uptake and increased fatty acid synthesis (39)(40)(41). In Group 2 macrophages of COVID-19 patients, two metabolic analysis methods both showed that glycolysis, fatty acid metabolism, bile acid synthesis and purine and pyrimidine metabolism were upregulated and strongly correlated to the cytokine and inflammation scores.…”
Section: Discussionmentioning
confidence: 99%
“…The term “Immunometabolic reprogramming” here refers specifically to the manipulation of the metabolism, immune function, and the relationship between the two by a virus in the host. Energy metabolism underlies an excessive immune-inflammatory response and plays a key role in controlling immune cell phenotype and function [72] . Immunity and metabolism are two highly integrated and interdependent systems, and balancing them is key to maintain the normal state of the body.…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%
“…The term “immunometabolism” has been used to explain the close relationship between metabolic regulation and immune function. Immunometabolic reprogramming is a mechanism by which immune cells promote cell proliferation and differentiation and exert immune effects by changing immune function and metabolic patterns to meet energy needs [72] . Immunometabolic reprogramming caused by a viral infection not only facilitates viral replication, but also antagonizes host antiviral responses associated with the immune system.…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%